(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the application of the ISO 22000 food safety management system in the field of oil and fat production, its implementation requirements and effectiveness. The relationship of the ISO 22000 standard with the HACCP principles, its role in identifying and controlling hazards in oil and fat enterprises is highlighted.